Experimental and simulation results of optical beam induced current technique applied to wide bandgap semiconductors. (May 2019) - Planson, Dominique; Asllani, Besar; Phung, Luong-Viet; Bevilacqua, Pascal; Hamad, Hassan; Raynaud, Christophe
Abstract: Power electronic devices based on wide bandgap (WBG) semiconductors such as silicon carbide (SiC), gallium nitride (GaN) and diamond (C) offer better performances when compared to those based on silicon (Si). However, the peripheral protection of these devices must be carefully designed to sustain high voltage bias. This paper shows how the OBIC (Optical Beam Induced Current) technique applied to WBG semiconductor devices could be useful to study the efficiency of different protection techniques. Firstly, a theoretical approach is given to present the this electro-optical characterization method. Then, it is performed on high voltage power devices in a vacuum chamber allowing to study the spatial distribution of the electric field in the semiconductor. In addition, comparisons with Finite Elements Methods using TCAD tools are performed showing the local high electric field strength. Results are mainly focused on SiC devices for the sake of availability. This paper shows additional results and measurements on GaN and diamond Schottky diodes also. Finally, extraction of OBIC signals allows to know some physical features like ionization coefficients, minority carrier lifetime and local defects in semiconductors as shown in the last section.